2020
DOI: 10.1136/bmjsem-2020-000892
|View full text |Cite
|
Sign up to set email alerts
|

Overuse injuries in the knee, back and hip of top elite female alpine skiers during the off-season preparation period: prevalence, severity and their association with traumatic preinjuries and training load

Abstract: ObjectivesTo investigate knee, back and hip overuse injuries in top female elite alpine skiers during the off-season preparation, which has so far received little attention, and to assess their relationship with traumatic preinjuries and overall training load.MethodsA cohort of 26 females of the Swiss Alpine Ski-Team were prospectively surveyed by the use of the Oslo Sports Trauma Research Centre questionnaire. Along with the surveys also total training loads were monitored. Data on preinjuries were assessed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Overuse injuries in elite alpine skiers are common in the off–season and preparation period, and hip injuries are the third most prevalent behind knee and lumbar spine injuries. 13,14 In a previous study evaluating hip pathology and the mechanisms of injury in skiers and snowboarders who underwent surgical treatment, the authors found high–speed crashes to be common in alpine racers and aerials athletes, with labral tears and FAI revealed at surgery. 19 Cam hip morphology is additionally more prevalent among this population when compared with nonelite skiers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overuse injuries in elite alpine skiers are common in the off–season and preparation period, and hip injuries are the third most prevalent behind knee and lumbar spine injuries. 13,14 In a previous study evaluating hip pathology and the mechanisms of injury in skiers and snowboarders who underwent surgical treatment, the authors found high–speed crashes to be common in alpine racers and aerials athletes, with labral tears and FAI revealed at surgery. 19 Cam hip morphology is additionally more prevalent among this population when compared with nonelite skiers.…”
Section: Discussionmentioning
confidence: 99%
“…19 Hip pathology in this high-demand group of athletes can drastically affect their performance and progress to worsening degeneration of the hip if underlying impingement is not adequately addressed. 16,17 Few studies have examined the prevalence of hip injuries in skiers and snowboarders, [13][14][15]19 and no studies, to our knowledge, have evaluated outcomes in individuals in this unique population who have undergone hip arthroscopy for FAI. The minimally invasive nature and advances in hip arthroscopic techniques have provided athletes a relatively rapid to return to sports at their preinjury levels.…”
Section: -In-5mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Studies on adult elite skiers showed that overuse-related back complaints occur both in the preparation phase (off- and on-snow training) and during the competition season. 11,12…”
mentioning
confidence: 99%
“…2 Studies on adult elite skiers showed that overuse-related back complaints occur both in the preparation phase (off-and on-snow training) and during the competition season. 11,12 The role of the lumbar multifidus (LMF) in overuse-related back complaints has been studied extensively. 10 LMF size, more specifically anatomical cross-sectional area (ACSA), appears to be a relevant variable in low back pain.…”
mentioning
confidence: 99%